Analisis Proses Pemeriksaan dan Perbaikan Sepeda Motor di Bengkel AHASS Toba Motor dengan Metode FMEA (Failure Mode And Effect Analysis) dan RCA (Root Cause Analysis) - Yunas Gosander Beremana; Muhammad Zakaria; Trisna Trisna (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to identify potential failures in the inspection and repair process at AHASS Toba Motor Workshop, determine the level of risk using the Failure Mode and Effects Analysis (FMEA) method, identify the root causes using Root Cause Analysis (RCA), and propose improvement recommendations. This research employed a descriptive quantitative approach. Data were collected through observations, interviews, documentation, and questionnaires distributed to five respondents consisting of the workshop manager, cashier, senior mechanic, and junior mechanic. The FMEA method was applied by assessing severity, occurrence, and detection to calculate the Risk Priority Number (RPN), while RCA with the 5 Whys Analysis technique was used to identify the root causes of the highest-priority failures. The results indicate that several failure modes in the inspection and repair process have high-risk levels and require immediate corrective actions. The primary root causes include inadequate mechanic accuracy, limited technical experience and competence, insufficient supervision of standard operating procedure (SOP) implementation, and ineffective final inspection procedures.